HHS/CDC Legal Response to SARS Outbreak - James J. Misrahi; Joseph A. Foster; Frederic E. Shaw; Martin S. Cetron (Emerging Infectious Diseases, 2004)
Before the severe acute respiratory syndrome (SARS) outbreak, the Centers for Disease Control and Prevention’s (CDC) legal authority to apprehend, detain, or conditionally release persons was limited to seven listed diseases, not including SARS, and could only be changed using a two-step process: 1) executive order of the President of the United States on recommendation by the Secretary, U.S. Department of Health and Human Services (HHS), and 2) amendment to CDC quarantine regulations (42 CFR Parts 70 and 71). In April 2003, in response to the SARS outbreak, the federal executive branch acted rapidly to add SARS to the list of quarantinable communicable diseases. At the same time, HHS amended the regulations to streamline the process of adding future emerging infectious diseases. Since the emergence of SARS, CDC has increased legal preparedness for future public health emergencies by establishing a multistate teleconference program for public health lawyers and a Web-based clearinghouse of legal documents.